High SARS-CoV-2 secondary infection rates in households with children in Georgia, United States, Fall 2020—Winter 2021 - Nowak, Kacy D.; Lane, Morgan A.; Mbanya, Armand; Carter, Jasmine R.; Binion, Brianna A.; Espinoza, Daniel O.; Collins, Matthew H.; Heaney, Christopher D.; Pisanic, Nora; Kruczynski, Kate; Spicer, Kristoffer; Rivera, Magdielis Gregory; et al. (Frontiers in Public Health, 2024)
Background: A wide range of household secondary infection rates has been reported, and the role of children in population transmission dynamics for SARS-CoV-2 remains ill-defined. We sought to better understand household infection at the early in the pandemic.A cross-sectional study of 17 households in the Atlanta metropolitan area with at least one child and one case of COVID-19 in the prior 1-4 months were recruited between December 2020 to April 2021. Self-collected saliva samples were tested on a multiplexed platform to detect IgG antibodies that bind to SARS-CoV-2 antigens. Secondary infection rates (SIR) were calculated and compared.We report results on 17 families, including 66 individuals. We found an average SIR of 0.58; children and adults were similarly infected (62% children vs 75% adults (p=0.2). Two out of 17 households had a pediatric index per our definition. Number of pediatric infections (p=0.18), isolation (p= 0.34), and mask wearing (p=0.80) did not differ significantly among households with an SIR above the mean vs those with SIR below the mean. Households with higher SIR also had a higher number of symptomatic cases (p<0.001).Discussion: We demonstrated high household SIRs at the early stages of the pandemic in late 2020 to early 2021 with similar impact on children and adults. The ease of collecting saliva and the detection of asymptomatic infections highlight the advantages of this strategy and potential for scale-up.